Tightrope - Marsh, Selina Tusitala (Auckland University Press, 2017)
Built around the abyss, the tightrope, and the trick that we all have to perform to walk across it, Pasifika poetry warrior Selina Tusitala Marsh brings to life in Tightrope her ongoing dialogue with memory, life and death to find out whether 'stories' really can 'cure the incurable'. Selina Tusitala Marsh draws on nursery rhymes, riddles, spells, Pasifika chants, popular song, rap - as well as on high modernist and postmodernist literature - to produce a new collection that is spiky and fierce, brash and vital, by turns, comic, irreverent, poignant, rhapsodic, anthemic, confrontational.